Biocomposites from anaerobically digested Eichhornia crassipes ((Mart.) Solms), as an alternative solution for the post-phytoremediation process - Gabriella Marsaulina; Taufik Taufikurahman; Andira Rahmawati (Current Research on Bioscences and Biotechnology, 2021)
Water hyacinth (Eichhornia crassipes) is a plant species commonly used for phytoremediation to reduce high chromium content in tannery liquid waste in Garut, West Java. Water hyacinth materials harvested from the phytoremediation can be used for the anaerobic digestion process to produce biogas and bio-slurry. This study aimed to determine the reduction of chromium content found in water hyacinths due to the anaerobic digestion process, and utilization of bio-slurry from the anaerobic digestion process as a biocomposite material. The anaerobic digestion process was carried out for 33 d using biodigesters and the composition of the biodigesters were varied into 100% dried water hyacinths and 80% water hyacinths with the addition of 20% cow dung. The bio-slurry from the anaerobic digestion process was then used for making biocomposites with 3 different compositions, i.e., 75 and 25%; 50 and 50%; and 25 and 75% of cement and bio-slurry, respectively. The average chromium content found in water hyacinths from the phytoremediation process without anaerobic digestion process was 41.964 mg/l. The results show a reduction in the amount of chromium after the anaerobic digestion process was found in each composition of bio-slurry, which were 15.979 mg/l (100% water hyacinth) and 14.861 mg/l (80% water hyacinth + 20% cow dung). Biodigester with a composition of 80% water hyacinth + 20% cow dung produced the highest average volume of biogas which was 0.424 l. The biocomposite of 75% cement and 25% bio-slurry had the highest compressive strength value of 30.598 MPa and water absorption capacity of 37.25%. It can be concluded that biocomposite with the composition of 75% cement and 25% water hyacinth bio-slurry is promising to be used as an alternative material for buildings.